ANTIDIABETIC ACTIVITY OF FLAVONOIDS: INTEGRATIVE REVIEW (REMUNOM, 2024)
Diabetes mellitus is characterized as a chronic disease resulting from high blood glucose levels (hyperglycemia), which occurs when the body does not produce enough of the hormone insulin. One of the natural methods for controlling diabetes is the use of bioactive products rich in substances known as flavonoids. This study consists of an integrative review and describes the antidiabetic activity of flavonoids. Fourteen articles published between 2000 and 2018 were selected. In all the selected studies, flavonoids were shown to be active in reducing glycemic indices and in the treatment of diabetes.